PHYSICAL AND CHEMICAL TEST OF CHILI PEPPERS (Capsicum Frutescens L) DRIED AT VARIOUS TEMPERATURES USING A DEHYDRATOR - Tira Jayanti; Devi Tanggasari (Protech Biosystems Journal, 2025)
Chili pepper (Capsicum frutescens L.) is a high-value agricultural commodity rich in vitamin C and antioxidant compounds. However, drying processes may potentially reduce its physical and chemical quality. This study presents novelty by investigating the effect of low-temperature drying using a dehydrator at 45°C, 50°C, and 55°C for 10 hours on changes in the physical and chemical properties of chili pepper, aiming to determine optimal drying conditions to maintain product quality and functional value. The parameters analyzed included weight loss, moisture content, vitamin C content, and beta-carotene content. The experiment was conducted using a Completely Randomized Design (CRD) with a single factor and three replications. The results showed that drying temperature had no significant effect on the physical and chemical characteristics of chili pepper. Drying at 55°C resulted in the highest weight loss (78.70%) and the lowest moisture content (15.9%). The highest vitamin C content was obtained at 45°C (76.58 mg/100  g), while the highest beta-carotene content was also recorded at 45°C (78.69 mg/100  g). Appropriate selection of dehydrator temperature can help maintain quality and extend the shelf life of dried chili pepper.